Pengaruh Komitmen Organisasional, Perencanaan Karir, dan Motivasi terhadap Kinerja Karyawan - Miswanto Miswanto; Eggi Sandy Tesa; Bambang Setia Wibowo (Telaah Bisnis, 2021)
This study aims to examine the effect of organizational commitment, career planning, and motivation on employee performance. Data collection was carried out through distributing questionnaires with 101 employee respondents who work in business organizations. The sampling technique used was purposive sampling and the data analysis method used was multiple linear regression. The results of this study indicate the following. Organizational commitment has no significant effect on employee performance. Career planning has a significant positive effect on employee performance. Motivation has a significant positive effect on employee performance. Simultaneously organizational commitment, career planning, and motivation affect employee performance.